The Effect of Cervical Cold-Knife Conization (CKC) on HPV Infection in Patients with High-Grade Cervical Intraepithelial Neoplasia: A Retrospective Study - Gao S; Huang L; Wang T; Wang J (Dove Medical Press, 2023)
Songkun Gao,1,2,* Lei Huang,1- 3,* Tong Wang,1,2 Jiandong Wang1,2 1Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing, 100026, People's Republic of China; 2Gynecologic Oncology Department, Beijing Maternal and Child Health Care Hospital, Beijing, 100026, People's Republic of China; 3Gynecology department, Yanqing Maternal and Child Health Care Hospital, Beijing, 102199, People's Republic of China*These authors contributed equally to this workCorrespondence: Tong Wang; Jiandong Wang, Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Qihelou Street, Dongcheng District, Beijing, 100006, People's Republic of China, Email fcyywt@ccmu.edu.cn; wangjiandongxy@ccmu.edu.cnPurpose: Investigation of HPV infection treatment in women undergoing cervical cold-knife conization for advanced cervical intraepithelial neoplasia.Patients and Methods: A retrospective analysis was conducted on patients who underwent cervical cold-knife conization for cervical intraepithelial neoplasia grade II-III at Beijing Obstetrics and Gynecology Hospital from January 2017 to December 2018. The HPV infection status of the patients at 6 months, 1 year, and 2 years after surgery was collected. We use chi square analysis and binary logistic regression to evaluate various factors such as age, number of pregnancies, number of cesarean sections, number of vaginal deliveries, HPV type, size of surgical specimens (diameter and height), and the influence of specimen edge on HPV infection.Results: A total of 334 patients were included in the analysis. The patients are mainly infected with HPV 16/58/52. Age is a influencing factor for HPV recovery 12 months after CKC surgery (P=0.002). Based on the diagnosis of HPV one year after CKC, the recovery rate of HPV58 patients is significantly lower than HPV16. Age is a influencing factor for the recovery of HPV infection (P< 0.05).Conclusion: The treatment of HPV infection by CKC is related to the patient's age and HPV subtype but not to number of pregnancies, number of pregnancies, number of vaginal deliveries, size of surgical specimens, and marginal conditions. The rate of HPV negative conversion is relatively high 24 months after the patient does not undergo surgery, but there is currently a lack of data on cervical lesions that match HPV results.Keywords: cold-knife conization, HPV infection, recovery rate, high-grade cervical intraepithelial neoplasia